Kinetic and Metabolic Isotope Effects in Zooxanthellate and Non-zooxanthellate Mediterranean Corals Along a Wide Latitudinal Gradient - Prada, Fiorella; Yam, Ruth; Levy, Oren; Caroselli, Erik; Falini, Giuseppe; Dubinsky, Zvy; Goffredo, Stefano; Shemesh, Aldo (Frontiers in Marine Science, 2019)
Many calcifying organisms exert significant biological control over the construction and composition of biominerals which are thus generally depleted in oxygen-18 and carbon-13 relative to the isotopic ratios of abiogenic aragonite. The skeletal δ18O and δ13C values of specimens of Mediterranean zooxanthellate (Balanophyllia europaea and Cladocora caespitosa) and non-zooxanthellate corals (Leptopsammia pruvoti and Caryophyllia inornata) were assessed along an 8° latitudinal gradient along Western Italian coasts, spanning ~2 °C and ~37 W m-2 of annual average sea surface temperature and solar radiation (surface values), respectively. Seawater δ18O and δ13CDIC were surprisingly constant along the ~850 km latitudinal gradient while a ~2 and ~4 ‰ variation in skeletal δ18O and a ~4 and ~9 ‰ variation in skeletal δ13C was found in the zooxanthellate and non-zooxanthellate species, respectively. Albeit Mediterranean corals considered in this study are slow growing, only a limited number of non-zooxanthellate specimens exhibited skeletal δ18O equilibrium values while all δ13C values in the four species were depleted in comparison to the estimated isotopic equilibrium with ambient seawater, suggesting that these temperate corals cannot be used for thermometry-based seawater reconstruction. Calcification rate, linear extension rate and skeletal density were unrelated to isotopic compositions. The fact that skeletal δ18O and δ13C of zooxanthellate corals were confined to a narrower range at the most isotopically depleted end compared to non-zooxanthellate corals, suggests that the photosynthetic activity may restrict corals to a limited range of isotopic composition, away from isotopic equilibrium for both isotopes. Our data show that individual corals within the same species express the full range of isotope fractionation. These results suggest that metabolic and/or kinetic effects may act as controlling factors of isotope variability of skeleton composition along the transect, and that precipitation of coral skeletal aragonite occurs under controlling kinetic biological processes, rather than thermodynamic control, by yet unidentified mechanisms.